PENGARUH BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BANK RAKYAT INDONESIA CABANG JAYAPURA - Muhamad Ohorela (ark:/00000/jeb.v12i1, 2021)
This study aims to determine and analyze the influence of the influence of workload on employee performance at PT Bank Rakyat Indonesia Jayapura Branch. employees at PT Bank Rakyat Indonesia Jayapura Branch. The sample in this study was 66 people, and the analytical tool used was simple linear regression. The results of this study indicate that the workload has a positive and significant effect on the performance of employees of PT. Bank Rakyat Indonesia Jayapura Branch. This is evidenced by the results of hypothesis testing which shows that the tcount value is greater than the ttable value and the significance level is smaller than the alpha value. Based on the results of the analysis in this study also found that workload has a strong relationship to the performance of employees of PT. Bank Rakyat Indonesia Jayapura Branch, where workload contributes 69% influence on employee performance.